Spiroplasma in Drosophila melanogaster Populations: Prevalence, Male-Killing, Molecular Identification, and No Association with Wolbachia - Ventura, Iuri M.; Martins, Ayana B.; Lyra, Mariana L. [UNESP]; Andrade, Carlos A. C.; Carvalho, Klelia A.; Klaczko, Louis B. (Springer, 2012)
Spiroplasma endosymbionts are maternally transmitted bacteria that may kill infected sons resulting in the production of female-biased broods. The prevalence of male killers varies considerably both between and within species. Here, we evaluate the spatial and temporal status of male-killing and non-male-killing Spiroplasma infection in three Brazilian populations of Drosophila melanogaster, nearly a decade after the first occurrence report for this species. The incidence of the male-killing Spiroplasma ranged from close to 0 to 17.7 % (so far the highest estimate for a Drosophila species) with a suggestion of temporal decline in a population. We also found non-male-killing Spiroplasma coexisting in one population at lower prevalence (3-5 %), and we did not detect it in the other two. This may be taken as a suggestion of a spreading advantage conferred by the male-killing strategy. Sequencing two loci, we identified the phylogenetic position of Spiroplasma strains from the three localities, showing that all strains group closely in the poulsonii clade. Due to intensive sampling effort, we were able to test the association between Spiroplasma infections and another widespread endosymbiont, Wolbachia, whose prevalence ranged from 81.8 to 100 %. The prevalence of Wolbachia did not differ between Spiroplasma-infected and uninfected strains in our largest sample nor were the prevalences of the two endosymbionts associated across localities.